Current status and prospects of potato processing in the Andean zone, implications for breeding and variety selection - Devaux, A.; Ordinola, M.; Suarez, V.; Hareau, G. (2024)
Main trends and perspectives of the processed potato sector in Latin America are analyzed, with emphasis on the Andean region (Bolivia, Colombia, Ecuador, and Peru); general information on Chile, Argentina and Brazil is also provided as a mean of comparison. Different market segments are described: chips, pre-fried frozen potatoes (domestic and imported), fresh cut potatoes and native potatoes. The data is generated from literature review, secondary sources (FAOSTAT and national statistics), technical sheets by country, interviews with 33 key informants linked to genetic improvement, markets and production managers of private potato processing companies, and a face-to-face workshop with more of 35 attendees. The findings seek to inform the objectives of genetic improvement in potatoes. Scenarios on trends and projections of the potato sector in the region and its productivity towards 2050 are also identified.